Penyuluhan Pemanfaatan Teknologi IoT dan AI pada Pertanian Melom Premium kepada Kelompok Satria Tani Hanggawana Kabupaten Tegal - Nurfahmi Fadlillah; Nurhadi Kamaluddin (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
The agricultural sector plays a crucial role in fulfilling food needs, but it continues to face several challenges, including limited land, climate change, and the need for more cost-efficient production methods. To address these challenges, the application of Artificial Intelligence of Things (AIoT) technology emerges as a promising solution to enhance productivity and efficiency in farm management. AIoT technology integrates artificial intelligence (AI) and the Internet of Things (IoT), enabling smarter decision-making, automation, and real-time data analysis in agricultural practices. This community service activity aimed to provide AIoT technology training to the Satria Tani Hanggawana Farmers' Group in Kalisapu Village, Slawi Sub-district, Tegal Regency, focusing on premium melon cultivation. The methods used in the activity included presentations on relevant materials, an introduction to AI and IoT-based Smart Farming technology, hands-on practice in a greenhouse, and interactive discussions. These methods were designed to equip participants with practical knowledge about integrating AIoT technology into their agricultural operations, enabling them to apply it directly to melon cultivation. The results of the activity showed a significant increase in the participants' understanding of agribusiness management, basic bookkeeping practices, and the application of AIoT in melon cultivation. The participants exhibited high enthusiasm, actively engaging in discussions and successfully performing practical exercises. This training was effective in improving farmers' knowledge and motivating them to adopt AIoT technology in their farming operations. The program has been instrumental in encouraging the use of smart farming techniques, which can lead to more efficient and sustainable farming practices. It is recommended that ongoing support, including follow-up activities and further training, be provided to ensure the sustainability of the technology implementation and continue to improve local food security